ANALYSIS OF THE EPIDEMIOLOGICAL CLINICAL PROFILE OF GESTACIONAL SYPHILIS IN ANÁPOLIS - GOIÁS IN THE PERIOD OF 2012-2018 (CIPEEX, 2022)
SYPHILIS IS AN INFECTIOUS DISEASE CAUSED BY TREPONEMA PALLIDUM, TRANSMITTED - MAINLY - BY SEXUAL AND VERTICAL ROUTES. ITS MOST PREVALENT MANIFESTATIONS ARE THROUGH THE SKIN, MUCOSA, CARDIOVASCULAR SYSTEM AND CENTRAL NERVOUS SYSTEM. THE RECOMMENDED TREATMENT IS WITH BENZATHINE PENICILLIN, WITH VARYING DOSES DEPENDING ON THE STAGE OF THE DISEASE. THE MAIN PROPHYLACTIC MEASURES ARE SAFE SEXUAL INTERCOURSE WITH CONDOMS, TREATMENT OF PREGNANT WOMEN AND PARTNERS, AND EARLY DIAGNOSIS. THE OBJECTIVE OF THIS STUDY IS TO CHARACTERIZE THE CLINICAL-EPIDEMIOLOGICAL PROFILE OF GESTATIONAL SYPHILIS (SG) IN ANÁPOLIS - GOIS, DESCRIBED IN THE SINAN DATABASE, BETWEEN THE YEARS OF 2012 TO 2018. THROUGH THIS CHARACTERIZATION, IT IS INTENDED TO DESCRIBE THE AGE GROUP AND THE MOST PREVALENT ETHNICITIES IN GESTATIONAL SYPHILIS, AS WELL AS TO VERIFY WHEN THE DIAGNOSIS OF SYPHILIS OCCURRED AND WHETHER THE PREGNANT WOMAN AND THE PARTNER WERE TREATED. THIS IS AN EPIDEMIOLOGICAL, OBSERVATIONAL, DESCRIPTIVE AND CROSS-SECTIONAL STUDY OF A QUANTITATIVE NATURE. NOTIFICATION / INVESTIGATION PAPERS FOR GESTATIONAL SYPHILIS WILL BE USED IN THE SINAN DATABASE CORRESPONDING TO THE REPORTED CASES OF GESTATIONAL SYPHILIS IN ANÁPOLIS - GOIS FROM 2012 TO 2018. SYPHILIS IS STILL A PREVALENT DISEASE IN DIFFERENT AGE GROUPS,AND CAN BRING RISKS AND HARM TO THOSE WHO ARE INFECTED, AFFECTING NOT ONLY THE INDIVIDUAL'S QUALITY OF LIFE BUT ALSO THE PARTNERS AND CHILDREN OF SYPHILITIC MOTHERS. THUS, IT IS OF FUNDAMENTAL IMPORTANCE TO STUDY AND RESEARCH THIS DISEASE TO MAKE IT INCREASINGLY UNDERSTOOD AND COMBATED BY HEALTH PROFESSIONALS AND THE POPULATION IN GENERAL.
Keywords: Syphilis. Epidemiology. Prevention and control.